BEYOND MEDICINE: HOLISTIC NURSING INTERVENTIONS FOR ACUTE MYOCARDIAL INFARCTION - Layla , Mohammed Al-Najafi (American Research Journal of Nursing and Health Sciences (ARJNHS), 2023)
Acute myocardial infarction (MI) is a common and potentially fatal condition that requires prompt and effective nursing care. Nurses play a vital role in the diagnosis, management, and treatment of acute coronary syndromes. The provision of evidence-based nursing practice (EBNP) is crucial to achieving high-quality nursing care and management. This article presents a case study to illustrate the rationale and nursing practice evidence underlying a holistic approach to caring for patients with acute MI. The framework for comprehensive care and management includes a nursing assessment, diagnosis, planning, intervention, and assessment process. The article highlights the importance of nurses’ willingness to modify nursing practice when new evidence emerges. The findings emphasize the need for a holistic approach to care, which involves extensive monitoring and regular analysis of data to obtain situational awareness of the patient’s evolution and risk for complications. By using an evidence-based approach, nurses can provide high-quality care that supports positive patient outcomes.